2017
DOI: 10.1109/tcsi.2017.2701499
|View full text |Cite
|
Sign up to set email alerts
|

HEAL-WEAR: An Ultra-Low Power Heterogeneous System for Bio-Signal Analysis

Abstract: Abstract-Personalized healthcare devices enable low-cost, unobtrusive and long-term acquisition of clinically-relevant biosignals. These appliances, termed Wireless Body Sensor Nodes (WBSNs), are fostering a revolution in health monitoring for patients affected by chronic ailments. Nowadays, WBSNs often embed complex digital processing routines, which must be performed within an extremely tight energy budget. Addressing this challenge, in this paper we introduce a novel computing architecture devoted to the ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 55 publications
1
31
0
Order By: Relevance
“…A similar conclusion is drawn in [4] and [5], which propose an embedded platform for bio-signal processing in personal health monitors, an increasingly relevant domain with ultra-low power constraints [8]. Similarly to us, [5] describes a CGRA with multi-DP RCs operating in SIMD (single instruction-multiple data) mode. Their proposed strategy, however, is only beneficial when the same acceleration is requested by different processors, themselves executing in SIMD mode.…”
Section: Introductionsupporting
confidence: 54%
See 3 more Smart Citations
“…A similar conclusion is drawn in [4] and [5], which propose an embedded platform for bio-signal processing in personal health monitors, an increasingly relevant domain with ultra-low power constraints [8]. Similarly to us, [5] describes a CGRA with multi-DP RCs operating in SIMD (single instruction-multiple data) mode. Their proposed strategy, however, is only beneficial when the same acceleration is requested by different processors, themselves executing in SIMD mode.…”
Section: Introductionsupporting
confidence: 54%
“…Similarly to [5], we characterized the system components (including processors, memories and the i-DP CGRA) at the post-synthesis level, targeting a 65 nm UMC technology. The obtained energy parameters were then employed to annotate a cycle-accurate virtual platform (specified in SystemC), allowing fast whole-system simulations of entire applications.…”
Section: Experimental Evaluation a Experimental Setup And Bio-smentioning
confidence: 99%
See 2 more Smart Citations
“…However, bio-DSP often involves complex functions and hence introduces high power requirements. To address this challenge, previous works have shown that task-level parallelism, typically present in bio-DSP applications, can be leveraged by multicore architectures with Single-Instruction Multiple-Data (SIMD) capabilities [1], while the execution of computational hotspots (kernels) can be effectively supported by Coarse-Grained Reconfigurable Array (CGRA) accelerators [2] [3] [4]. Thanks to the faster and more efficient execution achieved with the aforementioned techniques, smart bio-DSP IoT systems can remain longer in deep-sleep mode, consequently reducing their energy consumption.…”
Section: Introductionmentioning
confidence: 99%